2010
DOI: 10.1080/00048623.2010.10721478
|View full text |Cite
|
Sign up to set email alerts
|

Loans, Logins, and Lasting the Course: Academic Library Use and Student Retention

Abstract: Activities and services that improve student engagement and retention in the higher education sector are important not only to individual students' success but also to university planning and funding. This paper reports on a study carried out to explore whether use of the library by new university students is associated with continued enrolment. Limited to commencing students in March 2010 at Curtin University, the study drew on demographic data from the university's enrolment system and instances of library u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 13 publications
1
52
0
Order By: Relevance
“…Other studies have concluded that library technology instruction improves student retention. Indeed, the more technologically-prepared students are, the more likely they will persist (Haddow & Joseph, 2010). The VAL report also pointed out the importance of the collegiate experience, which is evident in the attention placed on a student's sense of belonging in recent literature.…”
Section: Introductionmentioning
confidence: 93%
“…Other studies have concluded that library technology instruction improves student retention. Indeed, the more technologically-prepared students are, the more likely they will persist (Haddow & Joseph, 2010). The VAL report also pointed out the importance of the collegiate experience, which is evident in the attention placed on a student's sense of belonging in recent literature.…”
Section: Introductionmentioning
confidence: 93%
“…Personalised or carefully targeted programmes and services can contribute to improved student retention (Haddow and Joseph 2010;Mezick 2007). Problem-oriented research consultations based on real needs, scheduled when needs arise, provide greatest impact and efficiencies for researchers.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Gaby Haddow and Jayanthi Joseph built on this study with data from the ARL, IPEDS, and the National Center for Education Statistics (NCES) to analyze the relationship between student retention for one semester with checkouts, workstation use, and logins to library resources. 11 They determined that a higher proportion of the students who were not retained had no or limited library use. Although this study focused on a single semester, the authors suggested that a student's library use in the early weeks of the semester is associated with staying in school.…”
Section: Literature Reviewmentioning
confidence: 99%